Model Tata Kelola Keamanan Data pada Ekosistem Pendidikan Muhammadiyah: Sintesis ISO 27001:2022 dan Nilai PHIWM - Ady Suprayitno (Peradaban Journal of Interdisciplinary Educational Research, 2026)
Digital transformation requires educational institutions to manage data as a strategic asset to support learning and academic services, yet it simultaneously increases the complexity of security risks. Muhammadiyah, as an organization overseeing thousands of educational units, faces challenges with fragmented data security governance due to its federative organizational structure. This research aims to develop a federated data security governance model through the synthesis of the ISO/IEC 27001:2022 standard and the values of the Islamic Pedagogy of Life for Muhammadiyah Members (Pedoman Hidup Islami Warga Muhammadiyah or PHIWM). Utilizing a conceptual literature review approach with content and thematic analysis, this study examines international standards, normative organizational documents, and relevant scientific literature. The results formulate a "centralized policy and distributed execution" model that integrates strategic leadership, policy formulation, shared security services, and technical implementation at the educational unit level. This model offers a balance between organizational standardization and operational flexibility for educational institutions, grounded in the ethics of science and technology. This research contributes to the development of a value-based data security governance framework for the digital education ecosystem within Muhammadiyah and similar educational organizations. Transformasi digital menuntut institusi pendidikan mengelola data sebagai aset strategis untuk mendukung pembelajaran dan layanan akademik, namun hal ini juga meningkatkan kompleksitas risiko keamanan. Muhammadiyah, sebagai organisasi dengan ribuan Amal Usaha Muhammadiyah (AUM) di bidang pendidikan, menghadapi tantangan tata kelola keamanan data yang terfragmentasi akibat struktur organisasi yang federatif. Penelitian ini bertujuan menyusun model tata kelola keamanan data terfederasi melalui sintesis standar ISO/IEC 27001:2022 dan nilai Pedoman Hidup Islami Warga Muhammadiyah (PHIWM). Menggunakan metode conceptual literature review dengan analisis isi dan tematik, penelitian ini mengkaji dokumen standar internasional, dokumen normatif organisasi, dan literatur terkait. Hasil penelitian merumuskan model centralized policy and distributed execution yang mengintegrasikan lapisan kepemimpinan strategis hingga pelaksanaan teknis di tingkat unit pendidikan. Model ini menawarkan keseimbangan antara standardisasi kebijakan organisasi dan fleksibilitas operasional institusi pendidikan dengan landasan nilai etika IPTEK. Penelitian ini berkontribusi dalam pengembangan kerangka tata kelola keamanan data berbasis nilai bagi ekosistem pendidikan digital Muhammadiyah dan organisasi pendidikan serupa.